Peran Komunikasi Pemasaran Untuk Meningkatkan Loyalitas Pelanggan Di Red Studio - Kadek Wulandari Laksmi P; Lely Anggreyni Jawak; I G. N. Oka Ariwangsa; Komang Satria Wibawa Putra (Universitas Serang Raya, 2025)
In today's digital era, everything is digitalized in all aspects. The company can achieve success not only determined by the quality of products, services and services offered but also determined by the company's ability to ensure customer loyalty to remain loyal to use the services and products marketed. This service aims to understand how the role of marketing communication in increasing customer loyalty at Red Studio. The methods used in this service are, 1. observation 2. active participation 3. guidance and mentorinf 4. practical projects. The results obtained show that by implementing a more effective marketing strategy in the future, the company can strengthen long-term relationships with consumers.